Studi Pemanfaatan Abu Tanah Liat Bakar Asal Gunung Sarik Padang Sebagai Filler Pada Campuran Hot Rolled Sheet (HRS) – WC - Fauna Adibroto - (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2014)
Together with advancement in transportation technology, there is a need to study current technology on transportation. Various research have been conducted on pavement to achieve a strong, durable, and economic construction. One of the constructions is Hot Rolled Sheet – Wearing Course (HRS-WC) or widely known as thin concrete asphaltic layer. Concrete asphalt is a flexible pavement with high structural strength and widely used in Indonesia as road pavement. Therefore the characteristic of the mixture is highly affected by type and percentage of filler in the mixture. In the last two decades, design methods are developed based on analytical method which require stiffness modulus and structural values of the material. During this period many research have been conducted on the methods to improve performance of asphaltic concrete by modification of materials as well as material substitution.The main objective of this study is to evaluate the impact of substitution of standard filler of HRS-WC with clay mineral from Gunung Sarik, Padang, on Marshall properties parameters such as stability, density, VIM, VMA, VFB, flow, and MQ. This aim is achieved by analyzing Marshall properties of the mixtures.Our study shows that the substitution of standard filler with clay mineral from Gunung Sarik with variations from 25%, 50%, 75%, and 100% has no significant impact on optimum asphalt content and other Marshall properties such as Density, VIM, VMA, and Flow. These values do not vary from mixtures using standard filler.